2018
DOI: 10.3389/fimmu.2018.02921
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 Activation of Hepatic Stellate Cell Line Suppresses HBV Replication in HepG2 Cells

Abstract: There is limited information about the role of hepatic stellate cells (HSCs) in the liver innate immunity against hepatitis B virus (HBV) infection. We thus examined whether hepatic stellate cell line (LX-2) can be immunologically activated and produce antiviral factors that inhibit HBV replication in HepG2 cells. We found that LX-2 cells expressed the functional Toll-like receptor 3 (TLR3), activation of which by PolyI:C resulted in the selective induction of interferon-β (IFN-β) and IFN-λs, the phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…All double stranded RNA (dsRNA) stimulate TLR3 and RIG-I in a sequence independent fashion, which is impossible to silence completely without removing the ability of RNAi to drive cleavage of its target mRNA . TLR3 is a potent TLR in the innate response to HBV, ,, and TLR3 stimulation via dsRNA in vivo results in the same delayed HBsAg response as observed with GalNAc-RNAi compounds in the clinic (Figure ). Thus, the universal and delayed HBsAg response observed in participants with RNAi may reflect transcriptional inactivation of cccDNA via TLR3 as opposed to RNAi-mediated mRNA cleavage.…”
Section: Targeting Svps In the Clinic To Achieve Functional Curementioning
confidence: 95%
“…All double stranded RNA (dsRNA) stimulate TLR3 and RIG-I in a sequence independent fashion, which is impossible to silence completely without removing the ability of RNAi to drive cleavage of its target mRNA . TLR3 is a potent TLR in the innate response to HBV, ,, and TLR3 stimulation via dsRNA in vivo results in the same delayed HBsAg response as observed with GalNAc-RNAi compounds in the clinic (Figure ). Thus, the universal and delayed HBsAg response observed in participants with RNAi may reflect transcriptional inactivation of cccDNA via TLR3 as opposed to RNAi-mediated mRNA cleavage.…”
Section: Targeting Svps In the Clinic To Achieve Functional Curementioning
confidence: 95%
“…Exposure of primary human hepatocytes or HepaRG cells to type-I IFNs or IFNLs reduced open-circle and cccDNA by causing cccDNA deamination and degradation, a phenotype attributed to induction of APOBEC deaminases [136]. Activation of stellate cell lines through toll-like receptor 3 resulted in induction of type-I IFNs and IFNLs, which inhibited HBV replication in HepG2 cells transfected with an HBV plasmid [137]. Finally, administration of pegylated IFNL1 in a xenograft model mouse model of human hepatocellular carcinoma led to reduced HBsAg expression in vivo [130].…”
Section: Ifnl Impact On Hbv Replication and Cccdnamentioning
confidence: 99%
“…In this regard, it has been reported that TLR-mediated antiviral activity is not limited to infected hepatocytes, but is also induced in hepatic stellate cells (HSCs) and peripheral blood mononuclear cells (PBMCs). Indeed, treatment of HepG2 cells with supernatants from poly(I:C)stimulated Lx-2 cells (HSC-derived cell line) inhibits the release of HBeAg and HBsAg in an IFN-b-dependent manner (105). Likewise, direct contact between HCV-infected hepatocytes and type 2 myeloid dendritic cells (mDC2) leads to the detection of dsRNA by TLR3 and the production of IFN-l (e.g., IL-28 and IL-29) (106).…”
Section: Sensing Of Hbv and Hcv Nucleic Acids In Hepatic Stromal Cellsmentioning
confidence: 99%